Excited-state regulated electroluminescence performance from thermally-activated delayed fluorescence (TADF) to hybridized local and charge-transfer (HLCT) emission. (September 2022) - Tian, Xuzhou; Yao, Mingming; Liang, Xinqi; Zhou, Changjiang; Xiao, Shengbing; Gao, Ying; Liu, Haichao; Zhang, Shi-Tong; Yang, Bing
Abstract: In this work, two novel D-π-A compounds (PXZ-FR-DRZ and CZ-FR-DRZ ) are designed and synthesized, aiming at the excited-state regulation from thermally-activated delayed fluorescence (TADF) to hybridized local and charge-transfer (HLCT) emission. This change of excited-state nature can be ascribed to the weakened electron-donating ability of carbazole relative to phenoxazine, together with the decreased twisting angle between carbazole and fluorine units. As a result of twisted charge-transfer (CT) excited state, the doped organic light-emitting diode (OLED) of PXZ-FR-DRZ demonstrates a blue-green TADF electroluminescence (EL) with a maximum external quantum efficiency (EQEmax ) of 11.5%, while its non-doped device shows a much lower EQEmax . Due to HLCT state of CZ-FR-DRZ, both its doped and non-doped OLEDs achieve the deep-blue non-delayed EL with the satisfied external quantum efficiency (EQE), especially for the excellent efficiency roll-off. Overall, this excited-state transformation between TADF and HLCT allows us to harvest the better comprehensive performance of OLED emitters for the practical applications, which provides a feasible solution for the development of OLED industry. Graphical abstract: Two different donors (phenoxazine and carbazole) are designed to match the same acceptor of 2, 4-diphenyl-1, 3, 5-triazine (DRZ) through a π-bridged linkage of 9, 9-dimethyl-9H-fluorene (FR), resulting in two novel D-π-A molecules of PXZ-FR-DRZ and CZ-FR-DRZ, respectively. The PXZ-FR-DRZ realizes a blue-green thermally-activated delayed fluorescence (TADF) with high external quantum efficiency (EQE) in the doped organic light-emitting diodes (OLEDs) due to the twisted charge-transfer (CT) excited state, whereas the CZ-FR-DRZ achieves a deep-blue non-doped OLED with the better comprehensive performance as a result of the hybridized local and charge-transfer (HLCT) state. Image 1 Highlights: Two D-π-A materials CZ-FR-DRZ and PXZ-FR-DRZ are synthesized with HLCT and TADF properties respectively. The TADF PXZ-FR-DRZ exhibits higher EQE than CZ-FR-DRZ. As an HLCT material, CZ-FR-DRZ displays high performance in non-doped OLED. The conversion between HLCT and TADF is investigated by changing different donors.